Professor Viorel Petrescu – A Professional Manager - Anca Atanase (Amfiteatru Economic)
For a long time, between 1992-2008, „the vice-rector of the Faculty of Commerce” – today, the Faculty of Business and Tourism – at the level of the management of The Bucharest University of Economic Studies was Professor PhD. Viorel Petrescu (1938-2023), the resort he assumed was for administrative, financial, and heritage activities, including the coordination of the Quality Management Department. In 1992 and 1995- 1996, for several months, he was also in charge of the Department of Commodities Science and Quality Management; in both cases, later being elected ViceRector, and, he had to quit his job as Head of Department. He has written 36 books and university courses, many contributions referring to the commodity expertise: Commodity Expertise, 1991, 2000 and 2002; Packaging and storage of goods: recapitulative schemes, 1996; Export-import commodity expertise, 2004; Expertise of commodity quality, 2005. It is awarded 45 research contracts with value, two patents for invention, four expertises. Under the guise of sobriety, he knew how to be cheerful. In 2009, I invited Professor Viorel Petrescu to create here the profile of his master, at least through the scientific leadership of the doctoral thesis (A Special Teacher - Professor Eng. Iosif Ionescu-Muscel). In the relentless passage of time, after 15 years, after the final surrender of the relay to the new generations, it is the turn of those who knew him (well) to highlight his personality. (Nicolae Lupu)